THE IMPACT OF THE TRANSITIVE ECONOMY ON THE DEVELOPMENT OF DOMESTIC ENTERPRISES - CHOBITOK, Viktoriya; DIERIABKIN, Andrii; DERIABKIN, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The transit economy today faces numerous challenges. This is the transformation of property as an institution through comprehensive privatization. In terms of its scale, this process has no analogues in world history. The end result is the creation of a national multi-proprietary system. In the process of transition from the state economy to the market economy mechanism, a new class of private owners was formed. During the entire period of reform, market economic institutions and mechanisms for coordinating the economic activity of economic institutions were created. The definition and redistribution of property rights gradually became the center of economic activity, especially at the level of domestic enterprises.In the conditions of global transformations of the 21st century. many countries faced the problem of finding a balance on the way to transition to a new type of development and ensuring the conditions of transitivity and global economic security. Guaranteeing economic security in one sense or another is a conceptual task of any state practically from the moment of its foundation. The issue becomes particularly acute in relation to the transitive economy, since the latter is characterized by numerous negative consequences of reform, which are manifested in the disintegration of production structures, the breakdown of economic ties, the imbalance between the extractive and processing branches of production, the collapse of the internal market, imbalances in regional development, and a decrease in the level of competitiveness national producers, etc. Phenomena, processes and trends recorded by mass consciousness, official statistics and scientific tools, which threaten the dynamic socio-economic development of Ukrainian society, raise the problem of economic security of development to a number of main strategic tasks.The purpose of the study is theoretical and applied substantiation of the impact of the transitive economy on the development of domestic enterprises.To date, the transitive economy can have a significant impact on the development of domestic enterprises due to changes in the conditions of competition, access to resources, sales markets and investments. Analysis of this impact can help to understand the prospects and challenges faced by domestic enterprises in the conditions of a transitory economy.Transitive economy (transitional) – economy during the historical period of changes in economic systems, the characteristics of which are complexity, instability, contradiction, inertia, intensive development of new economic forms; alternative transit economy means the process of movement of goods, services or capital through the territory of one country in order to deliver them to another country without their final processing or consumption in the territory of the first country. This includes the transportation of goods via railways, roads, seaports, airports or any other logistics route.These factors significantly affect the development of domestic enterprises, requiring them to adapt to new economic realities and search for ways to improve efficiency.Transitive economy, or the economy of the transition period, is a process of transition from a centralized planned economy to a market one. This process is accompanied by significant changes in economic structures, reforming of economic institutions, changes in forms of ownership and methods of enterprise management.During the time of independence, Ukraine went through various stages of transitive economy, which were characterized by significant changes in all spheres of economic life. The stages of the transitive economy significantly affect the activities of domestic enterprises, changing the conditions of their operation and identifying new challenges and opportunities.The impact of the transitive economy on the development of domestic enterprises is a multifaceted and deep process, which covers the transition from centralized planning to market mechanisms. In Ukraine, this transition took place since 1991 and was accompanied by numerous changes that had both positive and negative consequences for business. This process includes economic liberalization, privatization, structural reforms, financial stabilization, development of market relations, institutional reforms, social changes and integration into the world economy. Each of these elements plays an important role in the formation of a new economic system and determines the success of the transition to a transitive economy.In general, the transitive economy has created new opportunities for the development of domestic enterprises, while at the same time presenting them with a number of challenges. To ensure sustainable economic growth, it is necessary to continue reforms aimed at strengthening institutions, fighting corruption, supporting innovation and creating a favorable business environment. Only in the conditions of a stable and predictable economic policy will enterprises be able to fully realize their potential and make a significant contribution to the development of the transitive economy.
Keywords: transitive economy; development; domestic enterprises; factors of influence; economic activity